Formation of regional inter-sectoral complexes of recreation and tourism activity as a sign of structural reorganization of the economy - Vitaliy Sych; Victoria Yavorska; Kateryna Kolomiyets (Kazimierz Wielki University, 2021)
Changes taking place in recent decades in the global economy have led to the formation and development of new highly differentiated inter-branch complexes, rather than separated industries. In the global economy, such reorganization is marked by the formation of new sectors of the economy, one of which is a sector of socio-natural types of economic activity. At the level of regions, new integration formations are developed - regional inter-sectoral recreational complexes (IcRC). The purpose of our study is to substantiate the formation of regional inter-sectoral complexes of recreational and tourist activities (RTA) in the conditions of radical restructuring of the economy of post-industrial civilization. Inter-sectoral complex RTA is a set of different types of activities of the population - economic and non-economic, as well as leisure forms that provide the needs of the population of the region (countries) in recreation services, health improvement, healing and tourism, accompanying social services and recreational and tourist infrastructure. The study presents an author's vision of the composition and structuring of the regional inter-sectoral complex of recreation and tourism activity. The developed model of the inter-sectoral complex RTA covers all varieties of recreational activities with all its forms - tourism, organized recreation, unorganized (amateur) mass recreation, household recreation. The geographical bases for the formation of regional inter-sectoral recreational complexes are serving recreational and tourist resources - destinations that determine the specialization of the region by types of RTA. Depending on the level of development of RTA in the region, the RTA management systems may form. At the local and regional levels, the RTA nodes will be destinations - local and regional concentration of recreational and tourist resources with appropriate infrastructure. On the global (international) level, RTA retains a network form of a territorial organization, whose nodes are world centres and areas of tourism, as well as the main areas of formation of tourist flows.